IPad all-in-one for dummies - Muir, Nancy 1954- (John Wiley & Sons, 2012)
Six minibooks in one show you how to power-use the iPadFor work, play, and life on the road, the iPad has quickly become indispensable, and the new iPad is packed with even more features and power than ever. In this fun and practical guide, long-time For Dummies author Nancy C. Muir walks you through the latest functions, features, and capabilities of the iPad. Get up to speed on the basics, see how to use your iPad to get more organized and productive, learn to use your iPad for work, and discover all the ways to have fun. This book covers it all, and in full color!Packs six minibooks in one.
Print version record
Keywords: iPad (Computer); Pocket computers; Portable computers; Tablet computers; iPad (Ordinateur); Ordinateurs de poche; Tablettes électroniques; COMPUTERS; Hardware; Personal Computers; Macintosh; COMPUTERS; Hardware; Personal Computers; PCs